Investigation of Silica (SiO2) Nano Materials for Increasing Performance of Vehicle Radiator Cooling Systems - Arif Surono; Wachid Yahya; Adnan Nur Avif (Widyagama University of Malang, 2022)
This study aims to evaluate the effect of fluid flow rate on the effectiveness of radiator performance by using nanofluid consisting of a mixture of raw water with nano silica (SiO2) particles. The research was initiated by testing the silica material morphologically using a Scanning Electron Microscope (SEM) with the aim of knowing its microstructure. Next, mix the silica nanoparticles (SiO2) with water using a ratio of 0.5%, processed using a magnetic stirrer for 8 hours and precipitated for 24 hours. After being separated from the sediment, the nanofluid was tested for performance using a series of cooling system performance test equipment. A series of test equipment consisting of a radiator, flowmeter, water pump, pipe installation, heater and reservoir tank. Research data collection was carried out at the inlet and outlet temperatures as well as the radiator wall. In this study, variations in fluid flow velocity of 2.5, 4.5, and 6 LPM were carried out. The results showed that the decrease in temperature with the use of a fluid flow rate of 6 LPM was able to dissipate heat well to the environment. The decrease in temperature that occurs is 2.5%. Meanwhile, the lowest average radiator effectiveness value at the lowest speed of 6 LPM is 0.905, the highest at a fluid flow rate of 4.5 is 0.930.